What is the Best Index for Unemployment? - Habib-allah Shahriyari; Masoud Amiri; Zahra Shahriyari; Fatemeh Farzin (Shahrekord University of Medical Sciences, 2018)
A regular activity in all human societies is the evaluation and control of important socioeconomic indices. Unemployment rate is one of these indices, which is very important in evaluating and applying policies for control or preparation of desired changes in economy; in fact, it is a challenge for policy makers. Employment and unemployment are 2 words that have different definitions among people and professional centers of statistics. Since the statistics and methods applied for calculating Iranian employed and unemployed people have been provided by Statistical Center of Iran (SCI), the comparison of these definitions with recommended ones defined by International labor organization (ILO) may project 2 different items. In accordance with the definition of unemployment by ILO and SCI, each person who works at least 1 to 2 hours a week, even without receiving money, is considered as an employed person, otherwise is named as unemployed. Considering this definition, a new question may arise: in Iran, with consideration of location, subsistence, and labor market conditions, could people be satisfied with their living situation? Perhaps in some countries, this definition may be operational but not for Iranian worker community; in fact, no one in Iran and many other countries would be satisfied with one-hour work per week as an employed person.